Amor 2.0: ¿funcionan las parejas online? - Caciano, Carla (2019)
The article reviews the main concepts behind online dating and the numerous personal contact portals, as well as analyzes the results of various studies on couples born online. It also analyzes the current problems of couples formed through an online relationship.